The Effect of Increasing Running Speed on Mechanical Work of the Lower Limbs in Elite Male Runners - Yousefian Molla, Razieh; Molavian, Rozhin; Fatahi, Ali (Journal of Clinical Physiotherapy Research, 2022)
Introduction: Understanding the biomechanical performance of the lower limb joint during running is of the utmost importance for enhancing our current understanding of high human performance, as well as for identifying potential factors that may be associated with injuries. Given that the mechanical work of the lower limb joints conveys crucial information about joint function, the objective of the present study was to examine the impact of increasing running speed on the mechanical work of elite male runners. Materials and Methods: The current study is an observational cross-sectional study.28 healthy male elite runners aged 22 - 51 years ran on a treadmill with a force plate in the middle of the walk-way, at three different speeds, 2.5, 3.5 and 4.5 m/s respectively, and the data related to the mechanical work of the lower limbs were recorded and extracted. Also, in order to compare the averages of the Hip, Knee and Ankle mechanical work variables, ANOVA repeated measurements method with Bonferroni post hoc test was used. Results: It was found that increasing the speed leads to a significant difference in the mechanical work of the joints of the lower limbs including hip and ankle in both absorption and production phases(P<0.05) except in the knee joint at a speed of 3.5 to 4.5 in positive mechanical work (P=0.121). Conclusion: Considering the biomechanics of running is very important as a basic skill that every person performs during his life. The mechanical work aspects of the hip, knee, and ankle joints during increased running speed may potentially provide a biomechanical explanation for these clinical observations.